Third international open encounter on video. - CAYC - Centro de Arte Y Comunicacion, Buenos Aires; Galleria Civica d'Arte Moderna, Ferrara (Buenos Aires : Centro de Arte y Comunicación, 1975)
A.V.R. Art Video Recording ; Albright, David ; Alleyn, Edmund ; Alocco, Marcel ; Altmann, Roberto ; Amiard, Bernard ; Andersen, Eric ; Antin, Eleanor ; Arlandi, Gian Franco ; Arts Project ; Artworker Foundation ; Atchley, Dana ; Bal, Eduard ; Baladi, Roland ; Bauermeister, René ; Bealy, Alan ; Bentivoglio, Mirella ; Berkman, Phil ; Bernstein, Judith ; Bertrand, Jean-Pierre ; Bonnier, Alexandre ; Bonora, Lola ; Bottinelli, Bickhard ; Breloh, Heinz ; Burgy, Donald ; Byerley, Gerald ; Calame, Geneviève ; Cardazzo, Paolo ; Cardena-Warmingup, etc., etc. Company ; Carey, Tobe J. ; Carmi, Eugenio ; Caruso Turcato, Vana ; CAYC Group ; Cerberus ; Chartier, Gilles ; Chia, Sandro ; Chiari, Giuseppe ; Ciam, Giorgio ; Clareboudt, Jean ; Colette ; Copers, Leo ; Cort, David ; Coum Transmissions ; Courtois, Pierre ; Coutts-Smith, Kenneth ; Crivelli, Daniele & Naidi, Fabio ; Davidovich, Jaime ; Davis, Douglas ; Dean, Tom ; Dias, Antonio ; Dragan, Nusa in Sreco ; Dressier, Otto ; Druick, Don ; Druks, Michael ; Duck Jun Kwak ; Dujourie, Lili ; Dunn, Marty ; Edwards, James ; Ehrenberg, Felipe ; Environmedia ; Van Es, Hubert ; Evrard, Jacques ; Export, Valie ; Fabro, Luciano ; Fandangos Interview ; Fischer, Hervé ; Forest, Fred ; Fox, Terry ; Francis, Filip ; Geissler, Michael & Römer, Till ; Germana ; Gerz, Jochen ; Gette, Paul-Armand ; Giaccari, Luciano ; Gilbert, Gerry ; Glusberg, Jorge ; Goddamatch ; Goldman, Robert ; Great Georges Community ; Group CAP ; Group OBM ; Guyonnet, Jacques ; Hale, William Bruce ; Hansen, Al ; Hanson, Timothy ; Harding, Noel ; Hennesy, Sean ; Hlynsky, Dennis ; Hödicke, Karl Horst ; Hompson, Davi Det ; Hudson / Tava ; Hutchinson, Peter ; Imai, Norio ; Irick, K.C. ; Itter, Carole ; Journiac, Michel ; Kahlen, Wolf ; Kiser, Mel ; Klinkowstein, Tom ; etc.
Engels
Third international open encounter on video, CAYC - Centro de Arte y Comunicación, Buenos Aires / Galleria Civica D'Arte Moderna, Palazzo dei Diamanti, Ferrara, May 25th to 29th, 1975
boek